2014
DOI: 10.1017/s1041610214000842
|View full text |Cite
|
Sign up to set email alerts
|

The association of traumatic brain injury with rate of progression of cognitive and functional impairment in a population-based cohort of Alzheimer's disease: the Cache County Dementia Progression Study

Abstract: Background There is limited research on factors that influence the rate of progression in Alzheimer’s Disease (AD). A history of traumatic brain injury (TBI) is associated with an increased risk for AD, but its role on the rate of dementia progression after the onset of AD has not been examined. Method A population-based cohort of 325 persons with incident AD were followed for up to 11 years. The sample was 65% female with mean (sd) age of dementia onset = 84.4 (6.4) years. History of TBI was categorized as:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…However, a recent report utilizing a large (N = 51,799) TBI sample reported that a mild or moderate-to-severe TBI was associated with a higher risk for dementia, even after adjusting for several demographic, medical, and psychiatric factors [10]. In addition, TBI occurring later in life (i.e., within 10 years of AD onset), has been found to be related to higher risk estimates and more rapid decline after dementia onset [19]. Yet another related issue is that of repetitive TBI in relation to risk for cognitive decline later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent report utilizing a large (N = 51,799) TBI sample reported that a mild or moderate-to-severe TBI was associated with a higher risk for dementia, even after adjusting for several demographic, medical, and psychiatric factors [10]. In addition, TBI occurring later in life (i.e., within 10 years of AD onset), has been found to be related to higher risk estimates and more rapid decline after dementia onset [19]. Yet another related issue is that of repetitive TBI in relation to risk for cognitive decline later in life.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has emphasized the relationship between a history of TBI and AD [6,19,20], little is known about the potential impact of TBI on the development of MCI. For example, Guskiewicz et al (2005) reported a relationship between MCI symptoms and a history of three or more concussions in a small sample of retired athletes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Aβ levels are altered in cerebro-spinal and interstitial cerebral fluid in patients with TBI (Magnoni and Brody, 2010 ; Tsitsopoulos and Marklund, 2013 ) and correlate with clinical outcome (Magnoni and Brody, 2010 ). A history of TBI prior to the onset of dementia correlates with greater amyloid burden in patients with mild cognitive deficits (Mielke et al, 2014 ) and is associated with faster rates of cognitive decline in AD patients (Moretti et al, 2012 ; Gilbert et al, 2014 ). In TBI patients, APP transcription is upregulated and its axonal transport is interrupted due to diffuse axonal injury, which results in deposition of APP and its products in axonal “bulbs” (Hayashi et al, 2015 ).…”
Section: Traumatic Brain Injury App and Admentioning
confidence: 99%
“…Individuals who experience multiple concussions or sustain a single moderate to severe-TBI have a two-to fourfold increased risk of developing subsequent neurodegenerative diseases [5]. Furthermore, a history of TBI within 10 years of an ADRD diagnosis is associated with more rapid functional impairment progression [6].…”
Section: Introductionmentioning
confidence: 99%